Avaliação de diferentes potenciais interatômicos no cálculo do tensor de elasticidade do tungstato de zircônio - Chemello, Emiliano (My University, 2014)
Zirconium tungstate (ZrW2O8) is a material that exhibits negative thermal expansion (NTE), over a wide temperature range (0.3 at 1050 K). Although thoroughly studied, controversies still remain concerning the microscopic mechanisms responsible for this behavior. The cubic phase of this compound, denominated a-ZrW2O8, was already the subject of study through computer simulations using interatomic potentials (IP) and lattice dynamics in quasiharmonic approximation (LDQH). In two different IPs proposed in the literature succeeded in reproducing the a-ZrW2O8 NTE, but not the dependence with temperature of the elasticity tensor. Starting from this observation, this work intends to evaluate of existent IPs and same proposed new IPs in computer simulations aiming the calculation of the tensor of elasticity for a-ZrW2O8 between 0 and 300 K. Experimental data (such as atomic positions, lattice parameters and the tensor of elasticity of a-ZrW2O8 at 0 and 300 K) and, in another series of calculations, the ab initio energy hypersurface in the athermic limit, were used to obtain the parameters of the IPs. Different strategies were used in the search for the parameters of IP, including line minimization, Newton-Raphson/BFGS and genetic algorithm (GA). At the end of an exhaustive search we were led to conclude that it is not possible to describe the structure and elastic properties of a-ZrW2O8 as a function of temperature with simple IPs and that this incapacity is not related the any limitation of LDQH or of the parameters of the IPs, but instead to the analytical form of the tested IPs. This suggests that same results obtained with IPs already available in the literature may be unreliable. As alternatives for the solution of this problem, it can be considered the use of a neural network for the representation of the ab initio energy hypersurface, the use of more sophisticated IPs than take into account the atomic neighborhood (bond order potentials) and even (with a computational cost much higher) ab initio calculations at T > 0.
O Tungstato de Zircônio (ZrW2O8) é um material que exibe Expansão Térmica Negativa (ETN), isotrópica em um amplo intervalo de temperatura (0,3 a 1050 K). Apesar de amplamente estudado, existem controvérsias acerca dos mecanismos microscópicos responsáveis por este comportamento. A fase cúbica deste composto, denominada a-ZrW2O8, já foi motivo de estudo através de simulações computacionais utilizando Potenciais Interatômicos (PI) e Dinâmica de Rede na Aproximação Quasi-Harmônica (DRQH). Nos dois PI distintos propostos na literatura conseguiu-se reproduzir a ETN da a-ZrW2O8, mas não a dependência com a temperatura do tensor de elasticidade. É partindo desta observação que este trabalho pretende avaliar o desempenho de PI existentes e de novos PI em simulações computacionais visando a descrição da dependência com a temperatura do tensor de elasticidade da a-ZrW2O8 entre 0 e 300 K. Utilizaram-se dados experimentais, tais como posições atômicas, parâmetros de rede e o tensor de elasticidade da a-ZrW2O8 em temperaturas entre 0 e 300 K e, em outra série de cálculos, a hipersuperfície de energia ab initio no limite atérmico para obter os parâmetros dos PI. Diferentes estratégias foram empregadas na busca pelos parâmetros dos PI incluindo minimização em linha, Newton-Raphson/BFGS e Algoritmo Genético (AG). Concluiu-se que não é possível descrever as propriedades estruturais e elásticas da a-ZrW2O8 em função da temperatura com PI simples e que esta incapacidade não está relacionada a qualquer limitação da DRQH ou dos parâmetros dos PI, mas à forma analítica dos PI empregados. Isto sugere que se deve ter cautela na interpretação de resultados obtidos com estes potencias já disponíveis na literatura. Como alternativas para a solução deste problema, pode-se considerar o uso de redes neurais para a representação da hipersuperfície de energia ab initio, o uso de PI mais sofisticados que levam em consideração a vizinhança atômica (bond order potentials) e, também, cálculo ab initio a T > 0, este último a um custo computacional muito mais elevado.
Keywords: Engenharia de materiais e metalúrgica; Tungstato de zircônio; Expansão térmica negativa; Simulação computacional; Dinâmica de rede na aproximação quasi-harmônica; Tensor de elasticidade; Potenciais interatômicos; Zirconium tungstate; Negative thermal expansion; Computer simulation; Lattice dynamics in quasi-harmonic approximation; Tensor of elasticity; Interatomic potentials